Analisis Keterampilan Proses Sains pada Materi Stoikiometri - Savitri, Nadila Nur; Ad’hiya, Eka (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to determine the science process skills in groups on stoichiometry material. This type of research uses a descriptive method. The subjects in this study were all students of SMA Pusri Palembang Class XI who studied chemistry in the odd semester of the 2024/2025 academic year. The data analysis technique used quantitative descriptive. The results showed that of the 7 aspects of science process skills in stoichiometry material, there were three aspects that had the highest average values, namely observing 82%, measuring 80% and experimenting 81%. While the aspect that was classified as quite low was prediction skills at 63%. Based on these results, it can be concluded that the results of the analysis of students' science process skills in stoichiometry material as a whole with a value of 76% in the good category. This shows that the mastery of science process skills possessed by students is in accordance with the indicators that have been formulated previously. So that students are able to apply scientific theory knowledge in practice in the laboratory which includes observing, classifying, concluding, predicting, conducting experiments, and communicating.